Analisis Kebutuhan Fasilitas Sisi Darat Terminal 3 Bandar Udara Internasional Soekarno-Hatta Proyeksi Tahun 2025-2027 - Raga, Paulus; Irenita, Novembriani; Fitri, Nur Sagita; L, Bagus Adi (Institut Transportasi dan Logistik Trisakti, 2024)
Soekarno-Hatta International Airport, as one of the busiest air transport hubs in Indonesia, plays a crucial role in supporting national economic growth and mobility. With the increasing number of passengers, particularly at Terminal 3, an evaluation of the capacity and quality of existing facilities is necessary to ensure efficient and comfortable services. The study results indicate that currently, some facilities still meet IATA standards with a Level of Service (LOS) of A. However, passenger growth projections show a significant increase, with international passenger numbers expected to rise by 57.32% and domestic passenger numbers by 44.80% by 2027. As a result, several facilities are predicted to be inadequate to accommodate this growth, including departure kerbs, passport control, baggage claim areas, restrooms, seating, and parking capacity. This study highlights the importance of upgrading and adjusting terminal facilities to accommodate the future surge in passenger numbers, ensuring service quality and passenger satisfaction at the airport.